Segregated schools are the message (Revista Peruana de Investigación Educativa, 2021)
School segregation by socioeconomic status (SES) operates by grouping students from families similar in poverty or wealth. In Peru, school segregation by SES has grown a lot in recent decades, driven by market dynamics in education. Several studies have found that the level of poverty of students in each school is associated with the quality of school conditions and with the results in evaluations of learning achievements. This article reviews and discusses how the segregated condition and the location of each school in the SES stratified pyramid that is the Peruvian school system, operates as an implicit message and has effects on families, students, and society. Social composition is one of the criteria that families use to select the school for their children, along with some characteristics related to the expectations of the social group to which they belong or aspire to belong. For students, the segregated condition of their school is part of the hidden curriculum, which fosters certain representations, attitudes and values, different for each SES; it tends to hide or naturalize inequalities, justify privileges, reduce the expectations of the poorest young people, in addition to reducing social cohesion, increasing intolerance and discrimination of those who are different. It is recommended to deepen research on the effects of the experience of segregation by SES, which now prevails over the democratizing intentions of the official school curriculum.
Keywords: School; Educational grouping; Citizenship education; Democratization of education; Educational discrimination